2014
DOI: 10.1111/pedi.12151
|View full text |Cite
|
Sign up to set email alerts
|

Reduced morbidity at diagnosis and improved glycemic control in children previously enrolled in DiPiS follow-up

Abstract: Aims/hypothesis Children participating in longitudinal type 1 diabetes prediction studies were reported to have less severe disease at diabetes diagnosis. Our aim was to investigate children who from birth participated in the Diabetes Prediction in Skåne (DiPiS) study for metabolic status at diagnosis and then continued to be followed for two years of regular clinical care. Methods Children, followed in DiPiS before diagnosis, were compared to children in the same birth cohort who did not participate in foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Children who developed two or more islet autoantibodies were offered follow-up every 3 months with autoantibody sampling, HbA 1c , random plasma glucose and yearly oral glucose tolerance tests [6]. Children in follow-up were informed of risk after each blood sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who developed two or more islet autoantibodies were offered follow-up every 3 months with autoantibody sampling, HbA 1c , random plasma glucose and yearly oral glucose tolerance tests [6]. Children in follow-up were informed of risk after each blood sampling.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously described improved metabolic status at diagnosis and the 2 years after diagnosis for study participants [6]. The aim of this study was to examine whether the positive effect on metabolic control remains after the cohort has reached 5 years after diabetes diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, those favorable patterns of IDAA1c and C‐peptide were no longer apparent 1 year from diagnosis. Children followed before diabetes diagnosis within the DiPiS study had a lower HbA1c up to 2 years after diagnosis, compared with children diagnosed from the community . In the T1D Exchange Clinic Network, the overall frequency of detectable non‐fasting C‐peptide was 29%, with higher frequency in those diagnosed above age 18; residual secretion was present in almost 1 of 3 individuals 3 or more years from diabetes diagnosis …”
Section: Introductionmentioning
confidence: 99%
“…There are reports that children diagnosed with beta‐cell autoantibodies in longitudinal studies, in comparison with those in the community, required no or fewer hospitalizations, or had reduced frequency of ketoacidosis after being diagnosed . It has also been reported that participation in prospective follow‐up before diagnosis of T1D leads to earlier diagnosis with fewer symptoms, decreased incidence of ketoacidosis, as well as better metabolic control up to 2 years after diagnosis . Also, it cannot be excluded that several secondary prevention studies initially failing the end‐point such as parenteral and oral insulin in DPT‐1, nicotinamide in ENDIT, nasal insulin in DIPP, or hydrolyzed infant formula in TRIGR eventually may be successful perhaps through primary prevention or more effective intervention studies .…”
Section: Introductionmentioning
confidence: 99%